Gnosis und Spätantike Religionsgeschichte : Gesammelte Aufsätze - Rudolph, David (Nag Hammadi and Manichaean Studies, 1997)
A collection of 40 or so of the author's essays and contributions to the study of Gnosis, the Mandaeans and Manichaeism, published in the course of the past 40 years. Most have been revised for this new edition. Subjects treated include on the one hand source problems (Nag Hammadi, Manichaean finds and texts, Mandaean manuscripts), and on the other hand the situating of the gnostic-cum-Manichaean tradition in the context of late-antique religious history, especially with regard to the early Christian Church and its environment. Contributions on the history of research set out the issues and problems that have arisen from the study of these texts. Particular attention is given to the new finds from Nag Hammadi, which have proved highly significant for a new picture of Gnosis and Manichaeism. The author, who is especially well known for his work of Mandaica, has incorporated this aspect of Gnosis in the overall picture.